Vertalingstrategie met die oog op sinopsissamestelling - Zyl, Hermie C. van (Verbum et ecclesia, 1999)
Author is in the process of compiling a synopsis of the synoptic Gospels in Afrikaans. A new, literal translation is being made to serve the needs of synoptic comparison. This article deals with the translation strategy which follows. The strategy rests on two pillars: consistently rendering, as far as possible, a single Greek word by the same Afrikaans equivalent, and keeping as closely as possible to the Greek syntax. Various aspects and problems of this strategy are discussed, illustrated with numerous examples.